Single-Co Kondo effect in atomic Cu wires on Cu(111) - N. Néel; J. Kröger; M. Schüler; B. Shao; T. O. Wehling; A. Kowalski; G. Sangiovanni (Physical Review Research, 2020)
Linear atomic chains containing a single Kondo atom, Co, and several nonmagnetic atoms, Cu, were assembled atom by atom on Cu(111) with the tip of a scanning tunneling microscope. The resulting one-dimensional wires, Cu_{m}CoCu_{n} (0≤m,n≤5), exhibit a rich evolution of the single-Co Kondo effect with the variation of m and n, as inferred from changes in the line shape of the Abrikosov-Suhl-Kondo resonance. The most striking result is the quenching of the resonance in CuCoCu_{2} and Cu_{2}CoCu_{2} clusters. State-of-the-art first-principles calculations were performed to unravel possible microscopic origins of the remarkable experimental observations.